From Errata 5uite - Retallack, Joan (Current Musicology, 2013)
Errata 5uite. errant phrase denoting a succession of 5 line errata slips of tongue composed of letter notes written on 5 line musical staves (invisible) together forming a silent suite (Fr. a following).